Do allergic clinical manifestations increase the risk of behavioral problems in children? A cross‐sectional study. Issue 8 (7th July 2021) - Yamaguchi, Chikae; Ebara, Takeshi; Futamura, Masaki; Ohya, Yukihiro; Asano, Midori
Abstract: Background: Children with allergic clinical manifestations tend to have behavioral or emotional problems such as hyperactivity or worse mental health. However, previous studies on this association did not adequately adjust for confounders like parenting stress, demographic characteristics, or allergy presentation. This study aimed to investigate the relationship between childhood allergic clinical manifestations and behavioral problems, adjusting for confounders such as demographic characteristics, parenting stress, and allergy‐related variables. Methods: We conducted an online cross‐sectional survey among caregivers of children aged 2–6 years ( n = 633). The Strengths and Difficulties Questionnaire (SDQ) was used to determine children's behavioral characteristics as the primary outcome. Allergic clinical manifestations, wheeze, rash, and nose symptoms were the exposure variables. Associations were estimated using logistic regression analyses with propensity scores to adjust for confounders. Results: We analyzed 633 caregivers of children aged 2–6 years (valid rate, 61.5%). Univariate analyses showed that wheezing was associated with conduct problems (odds ratio [OR] = 1.48, 95% confidence interval [CI]:1.01–2.16), a behavioral component of the SDQ. Rash was also associated with hyperactivity (OR = 1.62, 95% CI: 1.02–2.57). Furthermore, nose symptoms were associated with conduct problems (OR = 1.65, 95% CI:1.16–2.33) and emotional symptoms (OR=1.62, 95% CI:1.06–2.45). After adjusting for potential confounders, wheezing (adjusted OR = 1.69, 95% CI:1.04–2.75) and nose symptoms (adjusted OR = 1.56, 95% CI: 1.05–2.34) remained associated with conduct problems. Conclusions: This study revealed that a history of wheezing and nose symptoms in children is associated with an increased risk of behavioral problems, in particular, conduct problems.